Planning to cheat: Temptation and self-control - Daniele Caliari; Ivan Soraperra (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Are opportunities making thieves? Accumulated experimental evidence shows that, when people have the opportunity to cheat, often they take it. Most of the literature on cheating opportunities forces people into a tempting situation where they face a trade-off between money and morality. In our paper, we ask whether people are sophisticated in their cheating behavior and whether they search for or avoid these trade-offs. Overall, participants in the experiment exhibit very little temptation, i.e., virtually no one is willing to pay a cost to avoid the possibility of misreporting in a coin-flip-like task, and they are able to consistently stick to their plan. Participants with a strict preference for the tempting situation, i.e., who are planning to cheat, show a winning rate of about 95% and those that are indifferent between having and not having the opportunity, i.e., who are planning to be honest, show a winning rate that is close to 50%.
Keywords: B41; C91; C93; 330; temptation and self-control; cheating; unethical behavior; lab experiment